2016
DOI: 10.1002/stem.2380
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Screening Identifies EUrd as a Novel Inhibitor Against Temozolomide-Resistant Glioblastoma-Initiating Cells

Abstract: Glioblastoma (GBM), one of the most malignant human cancers, frequently recurs despite multimodal treatment with surgery and chemo/radiotherapies. GBM-initiating cells (GICs) are the likely cell-of-origin in recurrences, as they proliferate indefinitely, form tumors in vivo, and are resistant to chemo/radiotherapies. It is therefore crucial to find chemicals that specifically kill GICs. We established temozolomide (the standard medicine for GBM)-resistant GICs (GICRs) and used the cells for chemical screening.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In this study, we identified fluspirilene as an agent inhibiting viability of GSCs and differentiated GBM cells, which demonstrated that our drug screening system was practical for the isolation of small-molecule compounds for the treatment of GBM. Tsukamoto et al designed a screening system for a unique compound library, containing nucleosides, sugars, peptides, kinase inhibitors, and natural products, using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay [ 23 ]. We adopted a screening system using existing drug libraries.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified fluspirilene as an agent inhibiting viability of GSCs and differentiated GBM cells, which demonstrated that our drug screening system was practical for the isolation of small-molecule compounds for the treatment of GBM. Tsukamoto et al designed a screening system for a unique compound library, containing nucleosides, sugars, peptides, kinase inhibitors, and natural products, using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay [ 23 ]. We adopted a screening system using existing drug libraries.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the efficacy of treatment, these mice received vehicle control (0.5% hydroxypropyl methylcellulose plus 0.2% Tween 80, and 20% dimethyl-sulfoxide (DMSO)) or combined treatment (20 mg/kg dabrafenib and 2 mg/kg trametinib solubilized in 20% DMSO) by oral gavage for 10 days. The tumors were measured daily with calipers, and tumor volume was calculated using the formula: Tumor volume (mm 3 ) = Length (mm) × Width (mm) 2 /2 [26]. Two additional mice from each treatment group were used for histopathological and Western blot analyses as described above.…”
Section: Methodsmentioning
confidence: 99%
“…NGT16, SF8628, U87MG, T98G cells were grown as adherent monolayer cultures in 10% FBS DMEM. SF7761, JHH-DIPG1 cells were grown as sphere cultures in EF20 medium composed with Neurobasal Medium (Thermo), 20 ng/ml EGF (Peprotech, Rocky Hill, NJ, USA), 20 ng/ml FGF (Peprotech), 2% B27 supplement (Thermo), 0.25% N2 supplement (Thermo), 3 mM L-Glutamine (Thermo), 2 µg/ml Heparin (Sigma), and 1% Antibiotic-Antimycotic (Thermo) (30,31).…”
Section: Establishment Of a Dmg Cell Linementioning
confidence: 99%